Comparative pharmacological and clinical review of selected herbal antihypertensive agents in hypertension management - Hemanga Mazumdar; Mrinmoy Basak (Creative Pharma Assent, 2026)
Background: Hypertension is a major global health concern and a leading risk factor for cardiovascular morbidity and mortality. Limitations associated with conventional antihypertensive therapy, including poor compliance, adverse effects, and inadequate blood pressure control, have increased interest in herbal agents possessing multitarget pharmacological actions and improved safety profiles. Methodology: A comparative literature review was conducted using PubMed, Scopus, Web of Science, Google Scholar, and ScienceDirect databases to identify relevant studies published between 2020 and 2026. Approximately 130 articles were screened, of which 80 relevant experimental studies, clinical trials, and meta-analyses were included for comparative evaluation of the antihypertensive effects, mechanisms, phytochemical profiles, and clinical relevance of selected herbal agents. Result and Discussion: Garlic (Allium sativum) demonstrated the strongest clinical evidence with consistent reductions in systolic and diastolic blood pressure through ACE inhibition, nitric oxide enhancement, and antioxidant effects. Ginger (Zingiber officinale) showed predominantly experimental evidence, with limited clinical evidence, of calcium channel blockade and vascular relaxation. Rauwolfia serpentina exhibited potent antihypertensive efficacy but was limited by neuropsychiatric adverse effects, whereas Terminalia arjuna provided moderate antihypertensive and cardioprotective benefits. Conclusion: Herbal antihypertensive agents exhibit mechanism-specific and stage-dependent therapeutic potential and may serve as supportive interventions in early-stage hypertension and cardiovascular comorbidities. However, the lack of standardization and limited long-term clinical evidence remain major limitations that require further investigation.